Chlamydomonas carries out fatty acid β‐oxidation in ancestral peroxisomes using a bona fide acyl‐CoA oxidase. (20th March 2017) - Kong, Fantao; Liang, Yuanxue; Légeret, Bertrand; Beyly‐Adriano, Audrey; Blangy, Stéphanie; Haslam, Richard P.; Napier, Johnathan A.; Beisson, Fred; Peltier, Gilles; Li‐Beisson, Yonghua
Summary: Peroxisomes are thought to have played a key role in the evolution of metabolic networks of photosynthetic organisms by connecting oxidative and biosynthetic routes operating in different compartments. While the various oxidative pathways operating in the peroxisomes of higher plants are fairly well characterized, the reactions present in the primitive peroxisomes (microbodies) of algae are poorly understood. Screening of a Chlamydomonas insertional mutant library identified a strain strongly impaired in oil remobilization and defective in Cre05.g232002 ( CrACX2 ), a gene encoding a member of the acyl‐CoA oxidase/dehydrogenase superfamily. The purified recombinant CrACX2 expressed in Escherichia coli catalyzed the oxidation of fatty acyl‐CoAs into trans ‐2‐enoyl‐CoA and produced H2 O2 . This result demonstrated that CrACX2 is a genuine acyl‐CoA oxidase, which is responsible for the first step of the peroxisomal fatty acid (FA) β‐oxidation spiral. A fluorescent protein‐tagging study pointed to a peroxisomal location of CrACX2. The importance of peroxisomal FA β‐oxidation in algal physiology was shown by the impact of the mutation on FA turnover during day/night cycles. Moreover, under nitrogen depletion the mutant accumulated 20% more oil than the wild type, illustrating the potential of β‐oxidation mutants for algal biotechnology. This study provides experimental evidence that a plant‐type FA β‐oxidation involving H2 O2 ‐producing acyl‐CoA oxidation activity has already evolved in the microbodies of the unicellular green alga Chlamydomonas reinhardtii . Significance Statement: Contrary to land plants, fungi and animals, the subcellular location and reactions of the fatty acid degradation pathway in microalgae are unclear. Here, we show that the green microalga Chlamydomonas employs a peroxisomal‐based and H2 O2 ‐generating pathway for fatty acid β‐oxidation. Physiological characterization of an acyl‐CoA oxidase mutant demonstrates that this pathway impacts significantly oil accumulation in Chlamydomonas .